Angola, meu t(r)emor: uma experiência autoetnográfica nos (des)encontros universidade-escola - Carolina Fernandes Archer (2023)
This research is contextualized within the relationship established between me, the researcherpartner, and two teachers from the rural area of Cabinda/Angola, in a universityschool partnership, as part of the UNISALE extension project which is linked to the Interfaces Program for Foreign Language Education at the Faculty of Letters of the Federal University of Minas Gerais. Specifically, the partnership was unfolded within the scope of the "UNISALE Vai Além" edition, over a period of 12 months, during which the partnerteachers and I (re)considered possibilities for their teaching practice. In Cabinda, both teachers faced challenges in their classrooms related to the absence of recognition of the region's multilingual context by the country's language and educational policies (BERNARDO, 2018). However, this research does not focus on the teaching materials produced by us or the potential subjective shifts experienced by the teachers in this process common aspects in other works in the field (CAMPOS, 2019; REIS et al., 2022, among others). On the contrary, this investigation is based on the assumption that the university must turn its scrutinizing gaze upon itself in order to achieve the objective of UNISALE, which is to reposition it in a relationship historically marked by colonial and hierarchical discourses (MATEUS, 2009). Thus, this research seeks to understand how my subjectivity as a researcherpartner was affected while engaging with the teachers from Angola. To this end, I employed autoethnography as a method and performance (ASSIS, 2018), as this approach allows researchers to explore how what affects them relates to sociocultural behaviors and practices (JONES, ADAMS, & ELLIS, 2013), offering a different perspective on phenomena that are often regarded as fixed. The research was conducted during the partnership through the narratives that constitute the corpus and during the writing of this text itself, where I conclude the autoethnographic performance. The discussion of various narrative excerpts grounded in Discourse Analysis (ORLANDI, 1999/2020) theory unfolds throughout the entire writing, dialectically relating to both theory and methodology, as it invokes and is based on them. The conclusions reveal that by becoming sensitive and receptive to the singular experience (LARROSA, 2014) of being present (BIESTA, 2017) with the other in partnership, I was affected in how I understand language, the researcher's practice, the university, and the partnership itself. In this sense, I transformed my understanding of language that constitutes the subject's identity, as the focus of my professional practice, as its possibility of minimum territoriality (HAESBAERT, 2004/2021). Lastly, as a result of these affectations, I argue that the researchersubject in a universityschool relationship must embrace their passions (LARROSA, 2014) in order for the university to be truly repositioned.